The role of the formation and destruction of the Hudson Strait glacial ice dam in changes of climate and sea level during the Last Interglacial-Glacial transition - Johnson, Robert G. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2021)
During the Last interglacial period of constant sea level, large coral reefs formed on the tectonically rising island of Barbados, and a broad lagoon with a small barrier reef formed at the Cane Vale site. The constant sea level was ended by a rapid glaciation, causing a fall of world sea level of 2.4 m, as measured by surveys of features associated with breaking waves on Barbados. The fall began about 120 ka BP, and lasted roughly 400 years, according to a lake pollen record from western Europe. That rapid fall was terminated at a wave-cut step on Barbados and with a quite small reversal in falling sea level. The rise was caused by rapid melting of the marine-based Barents Sea ice dome and other ice masses, due to a restored strong Atlantic Meridional Overturning Circulation (AMOC) flow. The sea level fall then resumed until it was halted at a wave-cut step at a world sea level 12.3 m below the last interglacial level, as recorded at the University of the West Indies site on Barbados. Following the erosion of that second step, a zonal northern North Atlantic circulation prevailed, causing a glacial ice-volume decrease and rise in sea level of 3.8 m. These two sea level fall reversals were caused respectively by the formation and destruction of a Hudson Strait ice dam and the resulting increase and much later decrease in the rate of AMOC flow.